2014
DOI: 10.18632/oncotarget.2945
|View full text |Cite
|
Sign up to set email alerts
|

SKP2 cooperates with N-Ras or AKT to induce liver tumor development in mice

Abstract: Mounting evidence indicates that S-Phase Kinase-Associated Protein 2 (SKP2) is overexpressed in human hepatocellular carcinoma (HCC). However, the role of SKP2 in hepatocarcinogenesis remains poorly delineated. To elucidate the function(s) of SKP2 in HCC, we stably overexpressed the SKP2 gene in the mouse liver, either alone or in combination with activated forms of N-Ras (N-RasV12), AKT1 (myr-AKT1), or β-catenin (ΔN90-β-catenin) protooncogenes, via hydrodynamic gene delivery. We found that forced overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Indeed N-Ras, another Ras family member, cooperates with molecules like Sphase kinase-associated protein 2 or AKT in promoting HCC in similar SB models. (19,20) Ras activation was also observed in the hMet-mutant-b-catenin model. (12) In the current study, we observe Ras activation in the G12D-K-Ras-S45Y-b-catenin and G12D-K-Ras-S33Y-b-catenin groups.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed N-Ras, another Ras family member, cooperates with molecules like Sphase kinase-associated protein 2 or AKT in promoting HCC in similar SB models. (19,20) Ras activation was also observed in the hMet-mutant-b-catenin model. (12) In the current study, we observe Ras activation in the G12D-K-Ras-S45Y-b-catenin and G12D-K-Ras-S33Y-b-catenin groups.…”
Section: Discussionmentioning
confidence: 78%
“…In our current study, activated K‐Ras (G12D‐K‐Ras) expression by itself did not yield HCC, suggesting that it may cooperate with another signaling pathway in tumorigenesis. Indeed N‐Ras, another Ras family member, cooperates with molecules like S‐phase kinase‐associated protein 2 or AKT in promoting HCC in similar SB models . Ras activation was also observed in the hMet‐mutant‐β‐catenin model .…”
Section: Discussionmentioning
confidence: 85%
“…The E3 ligase has been shown to be responsible for regulating the cellular level of p57 by ubiquitylation and proteolysis . Some evidence indicates that Skp2 could partly mediate p57 decreasing by a ubiquitin‐proteasome mechanism in HCC progression . Skp2 is responsible for regulating the cellular level of p57 via ubiquitylation by targeting p57 phosphorylated at mouse T329 (human p57 T310) .…”
Section: Discussionmentioning
confidence: 99%
“…(13) It has been reported that microRNAs, as well as the Akt and Skp2 pathways, can contribute to liver tumorigenicity, in part by p57 down-regulation. (14,15) However, the mechanism underlying p57 down-regulation in HCC has not been investigated to date.…”
mentioning
confidence: 99%
“…3a). Transgenic overexpression of Skp2 in the mouse prostate induces hyperplasia, dysplasia and low-grade carcinoma 31 , while co-expression of Skp2 with Nras G12V or myristoylated Akt1 in the mouse liver results in hepatocellular carcinoma (HCC) 32 . Conversely, Skp2 -knockout efficiently inhibits tumour development in a conditional Pten -deficient and Trp53 -deficient mouse prostate cancer model via activation of p27 KIP1 -dependent, p21 CIP1 -dependent and activating transcription factor 4 (ATF4)-dependent senescence 33 .…”
Section: Ubiquitin Ligases In Genome Maintenancementioning
confidence: 99%